Homiletik dan Retorika dalam Pewartaan Injil yang Bijaksana dan Menyentuh Hati - Atanasius Florentinus Tua; Antonio Fransisco De; Barnabas Kasi; Bertolomeus Ado Paga; Fransiskus Rendinatus Rake (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humani..., 2026)
The proclamation of the Gospel remains a central mission of the Church in every age. However, contemporary pastoral realities often reveal preaching that is overly theoretical, monotonous, and disconnected from the concrete struggles of believers. This study aims to examine the importance of homiletics and rhetoric in communicating the Gospel wisely and in ways that touch the hearts of listeners. The research employs a qualitative descriptive method through literature review by analyzing theological, communication, and pastoral sources related to preaching. The findings indicate that homiletics provides a systematic framework for interpreting Scripture, organizing messages clearly, and connecting biblical truth with daily human experience. Meanwhile, rhetoric strengthens delivery through effective language, voice modulation, credibility, emotional engagement, and persuasive communication. The study also finds that preaching becomes more meaningful when it is contextual, relevant to social realities, and presented with compassion and clarity. The integration of homiletics and rhetoric enables the Gospel to be proclaimed not merely as doctrine, but as a living message that inspires faith, hope, and moral transformation. Therefore, preachers are encouraged to develop both theological depth and communication skills so that the Gospel may remain relevant and transformative in the modern world